A new cross-overlapped decoupling coil structure for EV dynamic inductive wireless charging system / Yin Jia Lin - Keng , Ying Ying (2025)
The multi-transmitter and multi-receiver structure has been extensively discussed in Dynamic Inductive Wireless Charging (DIWC) systems for Electric Vehicles. Multiple coils have already been proven successful in high-power applications. Nevertheless, challenges persist in mitigating the adverse effects of cross-coupling among adjacent multi-coils and achieving higher transfer efficiency and stable output power under dynamic conditions. Thus, this paper proposes a new DIWC magnetic coupler consisting of a cross-overlapped transmitter and single receiver that serves multiple purposes, including decoupling, reduced mutual inductance fluctuation, and achieving high efficiency simultaneously. Moreover, the traversal method uses the finite element analysis tool ANSYS Maxwell to choose the optimized Rx coil turns and size, further improving system performance. A 2kW wireless charging setup is developed to validate the proposed DIWC magnetic coupler. The experimental results show that the output voltage fluctuation can be controlled within ±1%, and the maximum DC-DC efficiency is 92.87%. The longitudinal misalignment performance of the proposed DIWC magnetic coupler is also elaborated in this paper.